Espacio de consumo privilegiado: el territorio de comunicación publicitaria de la marca global - RIEGEL, Viviane (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2011)
The study of global brands comes within the field of communication in the action of these players, as message senders increasingly present in contemporary society. The texts and images of these brands are the scene of major cities around the world, talking to our daily lives. Brands´communication flows in their stores are a privileged consumption space, as constructed in its environment, where strategies in his speech are developed. To discuss this subject, the object of study are communication processes of McDonald’s brand in its stores around the world, analyzed as organized speeches from its own spatiality. The consumer proposition of meaning expressed by the global culture in their stores shows the socio-cultural dimension of the McDonald’s brand. Therefore, brand strategies are analyzed by the aesthetic dimension of their territory within systems of consumption. The methodology used to analyze the privileged consumption space of McDonald’s is the discourse analysis of the French line, applied under the categories of spaciality.